2012
DOI: 10.1248/cpb.60.743
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Fatty-Acyl Gratisin Derivatives

Abstract: To find candidates with high antimicrobial and low hemolytic activities, many gratisin (GR) analogues have been designed and synthesized. In the present account, we synthesized novel derivatives of GR having both the polycationic and fatty acyl groups, cyclo{-Val(1)-Orn(2)-Leu(3)-D-Phe(4)-Pro(5)-D-Lys(6)(X)-Val(7)-Orn(8)-Leu(9)-D-Phe(10)-Pro(11)-D-Lys(12)-} {X=-CO(CH(2))(6)CH(3) (1), -Lys-CO(CH(2))(6)CH(3) (2), -(Lys)(2)-CO(CH(2))(6)CH(3) (3), and -(Lys)(3)-CO(CH(2))(6)CH(3) (4)}, and examined the biological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…HBS buffer and 1 % triton X-100 were used as negative and positive controls respectively. [24] (See Supporting Information Section 6.2).…”
Section: Haemolytic Activitymentioning
confidence: 99%
“…HBS buffer and 1 % triton X-100 were used as negative and positive controls respectively. [24] (See Supporting Information Section 6.2).…”
Section: Haemolytic Activitymentioning
confidence: 99%
“…[18,19] It has become clear that the biological activity of GS is determined by a panel of physicochemical parameters: cationicity, hydrophobicity, amphiphilicity and hydrophobic aromaticity. [18] In the past decades, many strategies, including ring size variation, [20][21][22] β-turn modification, [23][24][25][26][27][28][29][30] β-strand modification [31,32] and light-controllable "smart" analogues [33][34][35] have been recognized as different routes to conceive new potent antimicrobial molecules endowed with low toxicity against human cells. However, to date, there is no clinically applicable antibiotic related to GS and thus a constant investment in this field is required.…”
Section: Introductionmentioning
confidence: 99%
“…Among the molecular approaches, we are particularly interested in the modification of D Phe-Pro motif in the β-turn region. Several studies have shown that even subtle changes in the β-turn region could have a dramatic impact on the biological profile, [26,27,32,36] suggesting this region is a promising target for modulating GS structure and activity. Both α-amino acids and unnatural dipeptide surrogates have been employed to substitute the native D Phe-Pro motif.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation